Kesiapan dan Dampak Penggunaan Teknologi Metaverse dalam Pendidikan - Brian Sebastian Salim; Filbert Ivander; Alex Cahyadi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Education in the 5.0 era provides significant changes to aspects of human development, especially in the world of education. The patterns and concepts of life in the metaverse era bring big problems if they don't get special attention and positive responses from the world of education. The main key to the progress of education towards world change is the nation's children. The majority of modern society has become part of technological life. Some schools have introduced the world of education with the involvement of technology. Difficulties in the learning process are felt by some educators who are not ready mentally, cognitively and facilities. This is an obstacle and a challenge for schools that do not have physical facilities or facilitators. The purpose of this research is to make a scientific contribution to the world of education in dealing with changes in various aspects of life. Research methodology with a qualitative type of design Narrative review. The results of the study explain that societal changes in the era of technological education have had positive and negative impacts. The role of educators in the utilization of education is the main responsibility in addressing the advantages and disadvantages. Information services and the application of the concept of understanding and being aware of change are the main components of positive thinking in utilizing technology quickly and correctly. In accordance with the functional pattern of using digital technology-based learning such as distance learning, monitoring of students in doing assignments and other social activities can be evaluated in a more planned and detected manner